Overview of the Implementation of Innovative Health Promotion Programs on Stunting Prevention in Adolescents - Annisa Fathulluluu; Budi Utomo; Woro Setia Ningtyas (Journal of Community Medicine and Public Health Research, 2026)
Stunting is a health problem that requires immediate attention to support the success of national development. Nutritional status will significantly influence the development of high-quality human resources in the future. Efforts to prevent stunting from an early age can be carried out through effective methods targeting youth. One of the health centers in Tasikmalaya district developed an innovation in health education, called GEN MULIA, to increase adolescents' knowledge and participation in the prevention and treatment of anemia from an early age. This study aims to describe the implementation of a health education program for adolescents. This research is descriptive with a qualitative approach. Data were collected through observation and in-depth interviews and analyzed using the Miles & Huberman approach. The population in this study was health workers and school teachers. This study showed that several considerations are needed for the health center to begin developing health promotion using digital media, including social media in the form of short videos that combine information and entertainment, which have been proven effective in increasing adolescents' knowledge. Selecting the correct method for implementing health education is very important, as it is essential to consider who receives it and the availability of time, funds, and health promotion personnel. Health promotion activities in schools should be carried out continuously and on target, given the many diseases for which health education is the only treatment.